Capturing student interest in software engineering through gamification: a systematic literature review - Matipa Ricky Ngandu; David Risinamhodzi; Godwin Pedzisai Dzvapatsva; Courage Matobobo (Springer, 2023)
Abstract ICT tools in education are widely used to support the aim of achieving learning outcomes by improving critical areas such as student engagement, participation, and motivation. In this study, we examine literature to explore how game elements are used in capturing students' interest, which the study suggests is fundamental to the teaching and learning of Software Engineering in higher education. Given the potential of alternative ICT tools such as flipped classrooms to increase interest in learning activities, there is a gap in similar literature on capturing interest in gamified environments, which has the potential to improve the achievement of learning outcomes. We applied flow theory to provide a guiding frame for our study. Following a systematic literature review for our data, we analysed 15 papers from the initial 342 articles, which were extracted from IEEE Xplore and Science Direct databases. The main finding in the reviewed papers underscores the positive impact of gamified learning environments on capturing student interest when teaching and learning Software Engineering. While the reviewed papers were not conclusive in identifying the best game elements for capturing students' interest, we found, that game elements such as points and leaderboards were the most common mechanisms used to advance students' interest when studying Software Engineering courses. The findings also suggest that different game elements are used in gamified environments to increase participation and engagement. The paper adds voice to the practical implications of gamification for teaching and learning. Although our study requires empirical evidence to validate our claims, we believe it sets the stage for further discussion. In the future, comparative studies of game elements in similar environments will be beneficial for identifying the ones that are more engaging and assessing their long-term impacts.